Health Education as a Strategy for Early Prevention of Sexually Transmitted Diseases human immunodeficiency virus - Sudirman Sudirman; Rikwan Rikwan; Sitti Fajrah; Subardin AB; Fitriani Fitriani; Sri Purwiningsih (Poltekkes Kemenkes Surakarta, 2022)
Background: In 2021, 203 cases of HIV infection, or 58% of the estimated 350 people, were found in Sigi District. Commitment and collaboration from every sector continue to be carried out to achieve